Academic and Digital Literacies and Writing in the Disciplines: A Common Agenda? - Parker, Jan (Journal of Academic Writing, 2011)
Reviewing keynotes and papers presented at the 2005, 2007 and 2009 EATAW conferences, and subsequent academic and digital literacies research, this paper considers the current agenda for academic writing teachers. It discusses pedagogic issues arising, for instance, from research on genre, multimodality, online communities, and the challenges and resources for the generation of students problematically called the ‘net generation’. Looking at two wings of academic writing research, those focusing on the ‘textual’ and those on processes and contexts, it raises the question of a common agenda for disciplinary writing studies, one exploring the transformatory processes and effects of disciplinary meaning making in ‘the digital university’.